2017
DOI: 10.1017/s0033291716003056
|View full text |Cite
|
Sign up to set email alerts
|

From neurological soft signs to functional outcome in young individuals in treatment with secondary services for non-psychotic disorders: a path analysis

Abstract: Our results provide evidence for a single pathway model in which the starting and intervening variables represent modifiable trans-diagnostic therapeutic targets to improve functional trajectories in young individuals with a recent-onset psychiatric diagnosis and different levels of psychosis risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…The authors also showed that NSS predicted a longitudinal decrease in the white matter integrity of the cerebello-thalamic tract that was associated with higher levels of negative symptoms. Consistent with the trans-diagnostic approach used in the current study, high levels of NSS have been associated with specific neural network abnormalities, cognitive dysfunction, negative symptoms and low functioning in both psychotic and non-psychotic individuals (Minichino et al, 2016a;Dazzan and Murray, 2002).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The authors also showed that NSS predicted a longitudinal decrease in the white matter integrity of the cerebello-thalamic tract that was associated with higher levels of negative symptoms. Consistent with the trans-diagnostic approach used in the current study, high levels of NSS have been associated with specific neural network abnormalities, cognitive dysfunction, negative symptoms and low functioning in both psychotic and non-psychotic individuals (Minichino et al, 2016a;Dazzan and Murray, 2002).…”
Section: Discussionsupporting
confidence: 76%
“…Third, a genetic marker improved the predictive model, suggesting that genetic markers may also have a relevant impact on functional outcome. Fourth, LF was not entirely dependent on the development of psychosis, further promoting the need for a broader trans-diagnostic approach in the field of functional recovery (Minichino et al, 2016a;Minichino et al, 2016b;Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to other dimensional constructs (e.g., psychotic-like experiences – PLEs), anhedonia and amotivation in otherwise “healthy” subjects might also have a clinical relevance per se as these symptoms are believed to predate the onset of a wide range of debilitating clinical conditions (psychosis, depression, substance misuse, chronic fatigue, and dementia) [ 5 , 6 ]. Shedding light on new treatment targets for anhedonia and amotivation is a clinical and research priority, as these symptoms still represent an unmet therapeutic need across diagnostic boundaries [ 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%